A Study on the Role of Advertisement to Promote the Business: Maximizing Sales through Effective Advertising (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Advertisement plays an important role in achieving growthin sales of product and services. Effective advertising refers to informing thepublic about the right product at the right time through the right medium. Theright media selection is the crux of the success of the entire advertisingcampaign. With more than two billion users around the world, the potentialreach alone has advertisers drooling.